Pendidikan Agama Islam Integratif Perspektif Gus Dur di Era Digital - Irsyad, Mohammad; Basri, Basri; Barizi, Ahmad (DIMAR: Jurnal Pendidikan Islam, 2025)
The chronic disease of scientific dichotomy seems to still infect some activists of Islamic religious education. This results in scientific discrimination in the form of extreme separation between "afterlife knowledge" and "worldly knowledge". The infection of this disease has the potential to be more severe if not treated immediately, considering the progress of the era that does not hesitate to crush anyone who cannot compromise with the digital era. The cure for this virus is found in the idea of integrative Islamic religious education initiated by Muslim scholars. Gus Dur is one of the intellectual figures who is loud in speaking about integrative Islamic religious education with a neo-modernist orientation. This study discusses integrative Islamic religious education from Gus Dur's perspective using a literature study method where this research is based on various literature spread across various platforms. The results of this study Gus Dur has a vision of Islamic religious education implemented in formal and non-formal institutions must be structured philosophically in terms of curriculum and learning materials by including three aspects of science; the classical Islamic scientific side, the traditional Indonesian scientific side and the modern scientific side. According to Gus Dur, all three must collaborate in harmony in order to produce the next generation who have competence in the field of Islamic and modern knowledge, appreciate local culture and can be wise in adapting to the progress of the digital era.